ANALISIS MANAJEMEN LOKASI PUSAT LOKASI PENGOLAHAN GABAH MENGGUNAKAN K-MEAN CLUSTERING DENGAN BAHASA PYTHON - MOEHAMMAD NASRI (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2023)
One of the interesting topics in operational management is the selection of processing centre locations. The right location will determine the efficiency of the results so that product prices will be competitive when entering the consumer market. Analysis of determining the location centre can use several methods, from simple using a spreadsheet to using a programming language. In this paper an analysis will be carried out to determine the location of grain processing centres (RMU, Rice Milling Unit) in Malang Regency. the analysis was carried out using the K-Means Cluster method in Python. With the input of spatial data on the location and area of rice fields in 390 villages in Malang Regency and the central estimating point variable (K): 4, 5 and 6. The results of the analysis obtained 6 proposed cluster centre locations that can be used as considerations in determining the location of agriculture-based businesses.